2008 International Conference on Cyberworlds 2008
DOI: 10.1109/cw.2008.124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Virtual Emotional Expression Systems for Human Robot Interaction in Rehabilitation Domain

Abstract: As rehabilitation robots are increasingly serving to improve the quality of life for physically disabled people in clinical environments, the concept of emotional expressiveness in robots becomes increasingly important. The human perception of robot's emotional expressions plays a crucial role in human robot interaction. Virtual expression systems outperform hardware systems in realizing human like expressions due the limitations in hardware actuators and advances in animation tools. This paper evaluates the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…DiSalvo and Gemperle (2003) suggested that the level of robotic anthropomorphism alters how individuals interact with robots. These influences include component elements, such as surface features (e.g., beveled edges, number of appendages; Sims, Chin, Yordon, et al, 2005), and facial features and expressions (Lum et al, 2007; Mohan, Calderon, Zhou, & Yue, 2008; Sims, Chin, Sushil, et al, 2005). Goetz, Kiesler, and Powers (2003) demonstrated that social cues are embodied in appearance and therefore influence how individuals perceive a robot (positively or negatively) as well as their willingness to comply with any instructions issued therefrom.…”
Section: Robot Intention: the Importance Of Anthropomorphismmentioning
confidence: 99%
“…DiSalvo and Gemperle (2003) suggested that the level of robotic anthropomorphism alters how individuals interact with robots. These influences include component elements, such as surface features (e.g., beveled edges, number of appendages; Sims, Chin, Yordon, et al, 2005), and facial features and expressions (Lum et al, 2007; Mohan, Calderon, Zhou, & Yue, 2008; Sims, Chin, Sushil, et al, 2005). Goetz, Kiesler, and Powers (2003) demonstrated that social cues are embodied in appearance and therefore influence how individuals perceive a robot (positively or negatively) as well as their willingness to comply with any instructions issued therefrom.…”
Section: Robot Intention: the Importance Of Anthropomorphismmentioning
confidence: 99%
“…Similarly, the degree to which a human will interact with a robot has been shown to be somewhat based on the robot's appearance (Li, Rau, & Li, 2010), as is its likeability (Goetz, Kiesler, & Powers, 2003). In other research, component-specific design preferences have been examined in regards to a robot's physical form such as preferred aesthetic features and appendages (Sims et al, 2005), facial features and expressions (Mohan, Calderon, Zhou, & Yue, 2008), and levels of anthropomorphism (DiSalvo & Gemperle, 2003). While there have been a number of studies exploring robot form, very few of these relate to trust (see Tsui, Desai, and Yanco, 2010 for one of the few studies examining anthropomorphism and human-robot trust).…”
Section: Robot Formmentioning
confidence: 99%
“…Many other developed and developing economies with rapidly growing elderly population are witnessing increasing case studies and developments in rehabilitation robotics targeted at reducing stress and depression in elderly (3) .…”
Section: Introductionmentioning
confidence: 99%